Phenotypic and genetic divergence in reed frogs across a mosaic hybrid zone on São Tomé Island. (19th September 2019) - Bell, Rayna C; Irian, Christian G
Abstract: Although naturally heterogeneous environments can lead to mosaic hybrid zones, human-induced habitat fragmentation can also lead to environmental heterogeneity and hybridization. Here we quantify phenotypic and molecular divergence across a reed frog mosaic hybrid zone on São Tomé Island as a first step towards understanding the consequences of hybridization across this heterogeneous landscape. The São Tomé giant reed frog ( Hyperolius thomensis ) is strongly tied to cool, wet, forest habitats whereas the distribution of Moller's reed frog ( H. molleri ) spans cool, wet, forests to warm, dry, disturbed habitats. Correspondingly, hybridization is concentrated in the more forested, cool, wet sites relative to non-forested, warmer, drier habitats. Four of six sites with hybrid frogs are artificial water bodies near the forest edge, indicating that both breeding habitat and broader scale environmental variation are probably important for understanding interspecific interactions and the extent of hybridization in this system. Phenotypic variation (body size and ventral coloration) largely tracks genetic and environmental variation across the hybrid zone with larger and more pigmented frogs occurring in forested, cool, wet habitats. Understanding whether human-induced changes in habitat break down reproductive barriers will be essential for conservation management of the less abundant, forest-associated H. thomensis in the face of rampant hybridization.